State-space Implementation in Forecasting Carbon and Gas Prices in Commodity Markets - Azhar, Rialdi; Kusuma Wisnu, Febryan; Satria Dwi Kesuma, Fajrin; Rizki Eka Putri, Widya; Andri Prasetya, Rian (International Journal of Energy Economics and Policy, 2022)
Carbon is a waste that becomes a new economic commodity. It has been traded like stock prices in commodity markets. Owing to its new status, research on carbon price movements as a new economic commodity linked to gas has gained a considerable amount of interest. A deeper observation of the future of world gas prices can also be an indicator of the stability of this commodity. We use the state-space model as a statistical basis for modeling the daily movement of carbon values ​​and gas prices. As a result, as we have calculated, the state-space model is able to predict and provide in-depth observational information on the relationship between carbon and gas. The economic implications show that carbon is not only good for the environment; its trading in the stock exchange also indicates that it can be a new stable and sustainable economic commodity.